What we harvest - Fraistat, Ann (Delacorte Press, 2022)
The farms of Hollow's End were blessed with miracle crops, especially the shimmering, iridescent wheat of Wren's family farm, but then the black mercury blight came, and the blight destroys everything: crops turned to silver-black sludge, animals sickened and blinded, even people; Wren believes she is responsible, and desperate to save Hollow's End she turns to her ex-boyfriend--but they find that there is a lot they do not know about their town and its miracle crops, and that their ancestors have a lot to answer for.